Managing Global Brands - Dhopeshwar, Nitin S. (Indian Journal of Marketing, 2009)
The innovative and aspiring marketers of 21st century are looking out for opportunities in the global market by creating and nurturing ’global’ brands. Creating a global brand and managing it is entirely a different thing. The global brands are those brands which have their presence in most of the global markets. They are termed as ’global’ by virtue of their recognition and acceptance in the different geographies of the world. Marketers who have ’big picture’ in their mind can only think of creating ’global’ brands. Global branding demands a lot of effort, commitment, resources, and passion. A marketer who aspires for owning global brands has to understand the markets and customer-needs in a crystal clear manner. There are many global brands present in the market and each have their own story of creation and performance. This article tries to bring out salient issues involved in creating, nurturing, and managing of global brands, with examples. It also deals with benefits available to the marketers and risks involved in developing global brands. The author intends to bring out the issues by referring to the information appearing in different journals, magazines, websites, etc. to create a knowledge on the topic.